Evaluating the efficacy and safety of various flaps in Autologous Breast Reconstruction: a Bayesian network meta-analysis - Li, Ling; Wu, Di; Zhu, Xiaohai (Frontiers in Medicine, 2024)
Aim This analysis evaluates the efficacy and safety of different flap techniques for Autologous Breast Reconstruction by collecting all clinical trials employing these methods and applying a Bayesian network meta-analysis. Materials and methods We systematically searched PubMed, Embase, and Web of Science for relevant literature, focusing on outcomes such as total flap loss, donor site wound dehiscence, secondary corrections at the donor site, psychosocial well-being, satisfaction with breasts, and sexual well-being. Results Our analysis included 10 clinical studies involving 871 patients across six flap techniques. In terms of total flap loss, the TUG flap showed the highest SUCRA value (89.6%), followed by the TMG flap (64.8%). For donor site wound dehiscence, the DIEP flap ranked highest with a SUCRA value of 60.1%, followed by the PAP flap (48.6%). In secondary corrections at the donor site, the PAP flap was the leader (95.5%), followed by the DIEP flap (52.5%) and the TMG flap (41.4%). For outcomes related to psychosocial well-being, satisfaction with breasts, and sexual well-being, the Four-flap technique consistently ranked highest (81.3, 85.0, and 88.4%, respectively). Conclusion Various flap techniques in Autologous Breast Reconstruction each present distinct benefits and risks. The Four-flap technique shows significant advantages in patient satisfaction, while the TUG flap excels in reducing total flap loss.